Increased red blood cell distribution width might predict left ventricular hypertrophy in patients with atrial fibrillation. Issue 37 (11th September 2020) - Yao, Hui-Ming; Wang, Xiao-Lei; Peng, Xiong; Chen, Shu-Yun; Wan, Xuan; Zuo, Wei; Gan, Xin
Abstract : Abstract: The presence of left ventricular hypertrophy has been confirmed to be an independent risk factor for stroke and death in patients with atrial fibrillation. This retrospective study aimed to evaluate the potential risk factors for left ventricular hypertrophy in patients with atrial fibrillation. A series of consecutive patients diagnosed with atrial fibrillation between June 2018 and December 2019 were included. The patients' clinical data were analyzed. The cut-off values, sensitivity and specificity of the independent risk factors were calculated using a receiver operating characteristic curve. Among 87 patients with atrial fibrillation, 39 patients with left ventricular hypertrophy and 48 patients without left ventricular hypertrophy were included. Multivariate logistic regression analysis showed that red blood cell distribution width (odds ratio [OR] 4.89, 95% confidence interval [CI]: 1.69–14.13, P  < .05) was an independent risk factor, while the concentration of low-density lipoprotein (OR 0.37, 95% CI: 0.17–0.83, P  < .05) and left ventricular ejection fraction (OR 0.88, 95% CI: 0.82–0.95, P  < .05) were inversely associated with left ventricular hypertrophy in atrial fibrillation patients. The receiver operating characteristic curve demonstrated that the area under the curve was 0.80 (95% CI: 0.71–0.90, P  < .05) with a cut-off value of 13.05, and the red blood cell distribution width predicted left ventricular hypertrophy status among atrial fibrillation patients with a sensitivity of 72.1% and a specificity of 76.9%. Red blood cell distribution width was associated with left ventricular hypertrophy in patients with atrial fibrillation.